Analisis Tingkat Kecakapan Hidup Dalam Perpektif Gender di Klub Bulutangkis Kota Bandung - Nabilah Wahidah; Mudjihartono -; Yusuf Hidayat; Burhan Hambali; Lilis Komariyah (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2023)
The purpose of this study was to analyze the level of life skills possessed by badminton athletes from sports clubs in Bandung using descriptive methods. A total of 44 athletes consisting of 31 male athletes and 12 female athletes participated in this study. The research instrument is the Life Skills Scale of Sport (LSSS), consisting of 47 items which were developed by Cronin to measure the level of life skills possessed by badminton athletes. The data obtained were analyzed using descriptive statistical analysis and independent sample T-test using SPSS software version 29.0. The results showed that the level of life skills for male athletes was the same as for female athletes. Both are in the high level category with a percentage of 72.73%. Based on gender, male athletes were in the high category with a percentage of 71.0% and female athletes were also in the high category with a percentage of 76.9%. Meanwhile, in the independent sample T-test analysis, the value of Sig. (2-Tailed) = 0.897. Based on these results, it can be seen that Sig. (2-Tailed) > 0.05, so there is no significant difference between the life skills of male athletes and female athletes. Key words: Badminton, Life Skills, Sport Coaching,